Comparative Analysis of Mercury Content in Canned Versus Fresh Indian Yellowfin Tuna Thunnus albacares - Lad, Devdatta; Fernandes, Benisha Estela Nellicia; D’Souza, Bliss Charles (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Heavy metals are categorized into essential and non-essential types, with the latter posing significant risks to human health, particularly Mercury (Hg), a non-essential metal known for its bioaccumulative and toxic nature. Thunnus albacares, commonly known as Yellowfin Tuna, is a high-trophic level carnivorous fish found abundantly in the Indian Ocean, making it a subject of concern for Mercury accumulation. The present study investigates the bioaccumulation of Mercury in the muscle tissue of T. albacares collected from the Mumbai coast, Maharashtra. Using spectrophotometric analysis with Stannous Chloride as the reducing agent, the Mercury content was determined and compared against established safety limits. The results indicate that fresh Tuna had a slightly higher Mercury concentration (0.14 ppm) compared to canned Tuna (0.13 ppm). Both values fall within the internationally accepted safety limit for Mercury in fish (0.3–1.0 ppm depending on guidelines), suggesting that the tested samples are suitable for human consumption. The Mercury in Tuna comes from the environment, where it is released into the water by industrial pollution and runoff from farms. Mercury can then be absorbed by plankton, which are eaten by small fish, which are then eaten by larger fish, such as Tuna. Hence, it’s the need of the hour that the release of Mercury in the aquatic ecosystem needs to be controlled.